Northwest Area Foundation Ventures Social Indicators Survey, June-September 2005 ([Verlag nicht ermittelbar], 2008)
The survey was designed to obtain information pertaining to community, neighborhood, local government, and community-based activities in an effort to discover ways to reduce poverty among the Ventures Communities (selected by the Northwest Area Foundation) in the Northwestern states of Idaho, Iowa, Minnesota, Montana, North Dakota, Oregon, South Dakota and Washington. Respondents were asked to identify their place of residence (state, county, and town) and length of time they had lived at that location, as well as a series of questions pertaining to their opinion about the community, the attitudes of persons within the community, and relationships between community members. The survey queried respondents about their community involvement and group memberships, and their connection with resources outside the community, and their neighbors, to solve inner-community issues. Respondents also appraised the quality of government services in the community, trust in local leaders and members of ethnic groups, the level of cooperation of community members in an emergency, and the effectiveness of individuals or organizations in reducing the number of people in poverty. For the next topic, respondents were asked to evaluate their personal or household financial status, such as their ability to obtain a loan, line of credit, or other financial services, and their ability to pay for basic living costs. Respondents were also asked whether they had received financial assistance from family, and to estimate the number of people or families in the community who could not afford basic living costs. The survey also asked respondents to identify their interest in public affairs, how frequently they accessed newspapers for information, and how often they voted in elections. Respondents evaluated how often young people move away to find better opportunities, their perception of safety while walking in the community at night, and the potential for the start up and growth of small businesses. In addition, respondents were asked about their health and quality of life. General demographic information includes: age, gender, race, religion and religious involvement, education, marital status, and employment status. Geographic information, in addition to location of residence, was obtained such as whether their residence was urban or rural, and whether or not they lived on or near an Indian reservation. Finally, household information was collected including household composition, income and current assets, the presence of a telephone or cell phone, and access to the Internet.